2015
DOI: 10.1063/1.4917206
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of driving frequency effect in low-pressure capacitively coupled oxygen discharges

Abstract: The effect of driving frequency on the electron density is investigated in low-pressure capacitively coupled oxygen plasmas by utilizing a floating hairpin probe. The power absorbed by the plasma is investigated and it is found that the power lost in the matching network can reach 50% or higher under certain conditions. The effect of driving frequency on the electron density is studied from two aspects, i.e., constant absorbed power and electrode voltage. In the former case, the electron density increases with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…However, in their experiment the power was fixed as the frequency was increased, and we have to assume that the electrode voltage dropped with increasing driving frequency. This has been seen by Liu et al [6] who kept the absorbed power fixed while the driving frequency was increased from 13.56 to 40.68 MHz and the electrode voltage deceased with increasing frequency to a minimum and then increases again with further increasing the driving frequency. Also, Colgan et al [3,5] reported a decrease in the electrode voltage with increased driving frequency while the discharge current is kept fixed in an argon CCP.…”
Section: Speciesmentioning
confidence: 61%
See 2 more Smart Citations
“…However, in their experiment the power was fixed as the frequency was increased, and we have to assume that the electrode voltage dropped with increasing driving frequency. This has been seen by Liu et al [6] who kept the absorbed power fixed while the driving frequency was increased from 13.56 to 40.68 MHz and the electrode voltage deceased with increasing frequency to a minimum and then increases again with further increasing the driving frequency. Also, Colgan et al [3,5] reported a decrease in the electrode voltage with increased driving frequency while the discharge current is kept fixed in an argon CCP.…”
Section: Speciesmentioning
confidence: 61%
“…However, it has to be kept in mind that at higher driving frequencies, standing wave and skin effects can limit process uniformity and power absorption in particular for large area processing in CCPs [8]. This was observed experimentally by Liu et al [6] in an oxygen CCP discharge, where under a constant electrode voltage condition the electron density increases with increased driving frequency in the frequency range 13.56-40.68 MHz and decreases as the frequency is increased further, due to lower power absorption as the frequency is increased above 60 MHz. The electron density has been suggested to scale roughly as the square of the driving frequency at constant rf voltage at fixed pressure and electrode separation [1,3,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their high relevance in material processing, oxygen CCPs have been studied extensively, both experimentally and by simulations [13,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. In pure oxygen CCPs, transitions between the α-mode and the DA-mode have been found by changing the gas pressure [13,14], the gap distance [14,17], the driving frequency [13,47], the driving voltage waveform [13,15,18,46,51,52], and the external magnetic field [49].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of this, it is more likely that the highly energetic SEs within the sheaths induce ionization rather than excitation. Due to their high relevance in material processing, oxygen CCPs have been studied extensively, both experimentally and by simulations [13,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. In pure oxygen CCPs, transitions between the α-mode and the DA-mode have been found by changing the gas pressure [13,14], the gap distance [14,17], the driving frequency [13,47], the driving voltage waveform [13,15,18,46,51,52], and the external magnetic field [49].…”
Section: Introductionmentioning
confidence: 99%